Pellynols M−O, cytotoxic polyacetylenic alcohols from a Niphates sp. marine sponge. Issue 27 (5th July 2018) - Wang, Jie; Liu, Li-Yun; Liu, Lei; Zhan, Kai-Xuan; Jiao, Wei-Hua; Lin, Hou-Wen
Abstract: Three new polyacetylenic alcohols, pellynols M−O (1 –3 ), along with two known ones, melyne A (4 ) and melyne B (5 ), were isolated from a Niphates sp. marine sponge collected off the South China Sea. The structures of new compounds were determined based on a combination of 1D and 2D NMR analysis, ESI-MS n fragmentation, and chemical (ozonolysis) method. Their absolute configurations were assigned by modified Mosher's method. All the isolates showed potent cytotoxic activity against PC9 and HepG2 human cancer cell lines with IC50 values of 2.9–7.6 μM. Graphical abstract: Image 1